Evaluasi Kualitas Jalur Pedestrian dengan Menggunakan Walkability Analysis di Jalan Kusuma Bangsa Surabaya - Diyah Ayu Saputri; Muhammad Andi Finaldi Nur Tantyo (G-Tech: Jurnal Teknologi Terapan, 2024)
The Jalan Kusuma Bangsa corridor is one of the corridors in the city of Surabaya which is filled with trade and service areas that have quite high activity intensity. The identity of this corridor is the Hi-Tech Mall and Taman Pemuda Surabaya. With these conditions, it is necessary to assess the friendliness of the Jalan Kusuma Bangsa road corridor using walkability analysis. This research uses a qualitative descriptive method to explore and explain the phenomenon in detail. The results of this research are the value of the walkability level of Jalan Kusuma Bangsa, Surabaya City using 7 criteria including Connected, Convivial, Conspicuous, Comfortable, Conveniet, Coexistence and Commitment.